Analisis Potensi dan Implementasi Biogas Skala Rumah Tangga di NTB dalam Mendukung Target Net Zero Emission Tahun 2050 melalui Pengurangan Emisi Karbon Sektor Peternakan - Krisna Wijaya; Sarjan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
West Nusa Tenggara Province (Nusa Tenggara Barat/NTB) has demonstrated a strong commitment to reducing greenhouse gas (GHG) emissions through various policies and strategic documents. However, among the many contributing sectors, the livestock sector—particularly cattle farming—has not received sufficient attention, despite its substantial contribution to GHG emissions in line with the increasing cattle population, which has exceeded 1.3 million heads. Improperly managed cattle manure contributes significantly to methane (CH₄) emissions, which have a much higher global warming potential than carbon dioxide (CO₂). This study aims to analyze the potential utilization of cattle manure as a biogas feedstock, estimate the amount of energy generated, and assess its contribution to GHG emission reduction in supporting the achievement of Net Zero Emissions (NZE) in NTB Province by 2050. The research employs a mixed qualitative and quantitative descriptive approach through literature review, secondary data analysis, and limited interviews with the NTB Provincial Office of Energy and Mineral Resources and the Regional Development Planning Agency (Bappeda). The results indicate that with 6,150 constructed biogas units utilizing approximately 12,300 cattle, the potential GHG emission reduction reaches 26,658.65 tons CO₂e per year, equivalent to about 0.625% of the total emission potential from the cattle livestock waste sector in NTB. This emission reduction is derived from methane (CH₄) emission avoidance and the substitution of fossil fuels such as liquefied petroleum gas (LPG). In addition to climate mitigation benefits, biogas utilization provides economic advantages through household energy savings and supports the implementation of a circular economy by utilizing bio-slurry as organic fertilizer. Although the current level of biogas utilization remains relatively low compared to its potential, biogas technology has proven to be a strategic and sustainable solution for livestock waste management, renewable energy development, and climate change mitigation efforts in NTB Province.